2021
DOI: 10.3389/fneur.2020.595532
|View full text |Cite
|
Sign up to set email alerts
|

Tau Post-translational Modifications: Dynamic Transformers of Tau Function, Degradation, and Aggregation

Abstract: Post-translational modifications (PTMs) on tau have long been recognized as affecting protein function and contributing to neurodegeneration. The explosion of information on potential and observed PTMs on tau provides an opportunity to better understand these modifications in the context of tau homeostasis, which becomes perturbed with aging and disease. Prevailing views regard tau as a protein that undergoes abnormal phosphorylation prior to its accumulation into the toxic aggregates implicated in Alzheimer's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
195
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(222 citation statements)
references
References 314 publications
3
195
0
Order By: Relevance
“…We observe K 317 to be ubiquitinated in AD, PrP-CAA (Q160X) and GSS (F198S), suggesting that the extra densities observed by cryo-EM near this residue in PrP-CAA (Q160X) and GSS (F198S) correspond to ubiquitination at this lysine. We also observe PTMs that have been reported to be important in Tau fibrillization and propagation in AD [27,28], for example, phosphorylation at T 231 , thought to be central to the initial steps of Tau detachment from microtubules and subsequent aggregation [1,2], is found in our cases of AD, PrP-CAA (Q160X) and GSS (F198S). We also observe PTMs within the two hexapeptide motifs, 275 VQIINK 280 and 306 VQIVYK 310 , which are known to be the minimum required motifs for Tau protein aggregation [39].…”
Section: Discussionsupporting
confidence: 69%
“…We observe K 317 to be ubiquitinated in AD, PrP-CAA (Q160X) and GSS (F198S), suggesting that the extra densities observed by cryo-EM near this residue in PrP-CAA (Q160X) and GSS (F198S) correspond to ubiquitination at this lysine. We also observe PTMs that have been reported to be important in Tau fibrillization and propagation in AD [27,28], for example, phosphorylation at T 231 , thought to be central to the initial steps of Tau detachment from microtubules and subsequent aggregation [1,2], is found in our cases of AD, PrP-CAA (Q160X) and GSS (F198S). We also observe PTMs within the two hexapeptide motifs, 275 VQIINK 280 and 306 VQIVYK 310 , which are known to be the minimum required motifs for Tau protein aggregation [39].…”
Section: Discussionsupporting
confidence: 69%
“…As a protein rich in lysine residues, tau has a high susceptibility toward ubiquitination. There are only three E3 ligases competent to ubiquitinated tau: The C-terminus of the Hsc70-interacting protein (CHIP), the TNF receptor-associated factor 6 (TRAF6), and axotrophin/MARCH7 [ 99 , 100 , 101 , 102 ]. Each of these E3 ligases ubiquitinates tau through different residues, suggesting that each ligase modulates tau degradation by different mechanisms.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…CHIP ubiquitinates tau through K48 or K63 residues and thus, regulates tau degradation via both proteasomal and autophagy systems. On the other hand, the E3 ligase TRAF6 ubiquitinates tau via K63, suggesting that ubiquitination mediated by this enzyme may regulate the degradation of tau in the ALP only [ 102 ]. However, phosphorylation of tau at alternative sites prevents ubiquitination and subsequent clearance [ 102 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Post-translational modifications (PTMs) of Tau such as phosphorylation, acetylation, ubiquitination, SUMOylation, methylation, and glycation have long been recognized as a critical contributing factor to tauopathies [ 17 , 18 , 19 , 20 , 21 ]. Tau PTMs may enable the formation of the highly ordered β-sheet structures, which facilitates the formation of filamentous Tau inclusions, as indicated by a recent study that reported a role of Tau ubiquitination in filament formation and strain specification [ 22 ].…”
Section: Astrocytes In Tauopathiesmentioning
confidence: 99%